Field Evaluation Efficacy of Acetamiprid Preparation against Bird Cherry-Oat Aphid (Rhopalosiphum Padi L.) and Impact on its Parasitoids - Alsabte, Ahmed; A. Isawi , Mohanad B; ismaeel KI, Omar; Mutar, H A (American Journal of Biology and Natural Sciences, 2025)
The bird cherry-oat aphid species (Rhopalosiphum padi L.) is the most frequent pest of winter wheat (Triticum aestivum L.). For the last few years, the attack of aphids on cereal crops has been increasing in Iraq, reducing cereal crop production [4]. Many types of pesticides have been used in wheat cultivation to control pests, and they are expensive, which causes social and environmental problems. There is an increasing demand to reduce the use of chemical insecticides and to search for ways and technologies to legalize and increase the efficiency of pesticides that affect pests while minimizing environmental damage. As a result, this study aimed to evaluate new acetamiprid preparations for application to the bird cherry-oat aphid (Rhopalosiphum padi L.). An experiment was performed to evaluate the effectiveness of six preparations on R. padi; it was observed that the new treatments have a close effect on the treatment of standard pesticide acetamiprid (ACT) and outperform it in one treatment, as shown in the treatment of (acetamiprid suspension) nanocapsules coated with chitosan (NCTCH). It also has little effect on parasitism and parasites in the field. New acetamiprid preparations are effective in killing the roles of wheat aphids, and they are environmentally friendly compounds that can be adopted in integrated pest management programs.